The Role of the Community Guidance Unit in Preventing Fraud Crimes Through Counseling in the Majalengka Police Jurisdiction - Krisnatha, I Putu Gede Denny (Advances in Police Science Research Journal, 2024)
The National Police of the Republic of Indonesia is a state institution that has three main tasks and has the duty and function to prevent crime, one of which is preemtive crime prevention against criminal acts committed in the jurisdiction of Majalengka Regional Police by conducting counseling because it is assessed the number of criminal acts of fraud in the region Majalengka police station law every year is a high number. Fraud is a criminal offense committed by an offender by persuading and seducing the victim for personal gain. In carrying out thesis writing, the author refers to the previous 2 theses by discussing the role of the binmas unit, the factors that influence counseling and what efforts are made by the binmas unit in preventing fraud through counseling with communication theory, crime prevention theory and the concept of counseling. The author uses a qualitative approach with a descriptive method by collecting data by observation, interview and document study conducted in Majalengka District which focuses on the role of the community service unit in preventing fraud through counseling which has two benefits, namely theoretical and practical. Majalengka is a regency which is a cross lane with an area of 1204.24 km, fraud cases in majalengka are the cases with the highest number that occurred in Majalengka Regency. The Community Protection Unit performs pre-emptive prevention based on crime prevention theory by conducting counseling to the community based on the concept of counseling and communication theory carried out by the Majalengka Police Binmas Unit. From the discussion, the writer has a suggestion that the Majalengka Police Binmas Unit can prevent fraud through counseling.